The Performative Arts and Pedagogy Project – Towards the Development of an International Glossary - Woodhouse, Fionn (SCENARIO: Journal for Performative Teaching, Learning, Research, 2019)
On the morning of 1st March 2019 a group of 22 people representing 5 different countries (Austria, Germany, Ireland, Switzerland, & the U.K.), gathered in the lively surroundings of the Creative Zone in Boole Library, University College Cork, with the express aim of developing a deeper understanding of the discipline-specific knowledge bases, ideas, and operational concepts associated with Performative Arts and Pedagogy. Through a range of working methods including discussion, group work, guest lecture and workshop the conference facilitated a systematic interdisciplinary and intercultural exchange working towards an increased awareness of (culture-)specific concepts and associated terminologies. Over the course of the 2 days these activities led to an heightened appreciation of variants, differences and similarities and paved the way towards the development of transcultural performative practices. This conference is a result of a number of meetings, initiated by the Bundesarbeitsgemeinschaft Spiel & Theater e.V., which took place in Berlin focusing on the need to engage with historical, current and future developments in the broad area of ‘Performative Arts and Pedagogy’. Also a panel discussion entitled ‘What Exactly is an Apple Pie?’ as part of the 4th Scenario Forum Symposium ‘Towards a Teaching, Learning, and Research Culture’ further highlighted the range ...